Surds question grade 9

I am a student and I need help answering this question.

Simplify:

$\frac{6}{\sqrt{28}}$-$\frac{9}{\sqrt{63}}$

What I did:

$\frac{6}{\sqrt{28}}$-$\frac{9}{\sqrt{63}}$

=$\frac{6}{\sqrt{7\times 4}}$ - $\frac{9}{\sqrt{7\times 4}}$

= $\frac{6}{2\sqrt{7}}$ - $\frac{9}{3\sqrt{7}}$

$\frac{6}{2\sqrt{7}}$ × $\frac{2\sqrt{7}}{2\sqrt{7}}$ = $\frac{12\sqrt{7}}{14}$

$\frac{9}{3\sqrt{7}}$ × $\frac{3\sqrt{7}}{3\sqrt{7}}$ = $\frac{27\sqrt{7}}{63}$

($\frac{12\sqrt{7}}{14}$)/2 = $\frac{6\sqrt{7}}{7}$

($\frac{27\sqrt{7}}{63}$) /2 = $\frac{3\sqrt{7}}{7}$

$\frac{6\sqrt{7}}{7}$ - $\frac{3\sqrt{7}}{7}$

= $\frac{3\sqrt{7}}{7}$

Thankyou and help is appreciated.

I am a student and I need help answering this question.

Simplify:

$\frac{6}{\sqrt{28}}$-$\frac{9}{\sqrt{63}}$

What I did:

$\frac{6}{\sqrt{28}}$-$\frac{9}{\sqrt{63}}$

=$\frac{6}{\sqrt{7\times 4}}$ - $\frac{9}{\sqrt{7\times 4}}$

= $\frac{6}{2\sqrt{7}}$ - $\frac{9}{3\sqrt{7}}$

$\frac{6}{2\sqrt{7}}$ × $\frac{2\sqrt{7}}{2\sqrt{7}}$ = $\frac{12\sqrt{7}}{14}$

$\frac{9}{3\sqrt{7}}$ × $\frac{3\sqrt{7}}{3\sqrt{7}}$ = $\frac{27\sqrt{7}}{63}$

($\frac{12\sqrt{7}}{14}$)/2 = $\frac{6\sqrt{7}}{7}$

($\frac{27\sqrt{7}}{63}$) /2 = $\frac{3\sqrt{7}}{7}$

$\frac{6\sqrt{7}}{7}$ - $\frac{3\sqrt{7}}{7}$

= $\frac{3\sqrt{7}}{7}$

Thankyou and help is appreciated.